2018
DOI: 10.14712/23363177.2018.279
|View full text |Cite
|
Sign up to set email alerts
|

Specific Effects of Language Transfer Promoting Teaching and Insights Into the Implementation in EFL-Teaching

Abstract: Abstract:The following contribution analyzes language transfer promoting instruction in the context of English as a foreign language (EFL) instruction in 9 th grade secondary classes in Germany . By combining data from questionnaires, tests, and video-data, the article sheds light on learning outcomes in the context of language transfer promoting instruction and presents teaching practice of interlanguage reflection in ESL-teaching. Results indicate a positive correlation of language transfer promoting teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Although future studies would have to explore the underlying psycholinguistic and/or motivational causes in more depth, results would have high practical relevance. Because addressing linguistic diversity in a resource‐oriented way is still an exception in the language classroom (see Göbel & Vieluf, ), our study may encourage teachers to try to incorporate students’ linguistic resources and help persuade those who show reticence about allowing or incorporating home languages in the classroom (see Bailey & Marsden, ). In addition, teachers may see the value of implementing affective‐experiential activities in linguistically diverse settings so as to foster positive affect and well‐being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although future studies would have to explore the underlying psycholinguistic and/or motivational causes in more depth, results would have high practical relevance. Because addressing linguistic diversity in a resource‐oriented way is still an exception in the language classroom (see Göbel & Vieluf, ), our study may encourage teachers to try to incorporate students’ linguistic resources and help persuade those who show reticence about allowing or incorporating home languages in the classroom (see Bailey & Marsden, ). In addition, teachers may see the value of implementing affective‐experiential activities in linguistically diverse settings so as to foster positive affect and well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…Creating an opportunity for students to make use of their linguistic resources in the classroom is also beneficial to their learning and for their developing multilingual competencies (Cenoz & Gorter, ; García, Ibarra Johnson, & Seltzer, ; García & Wei, ). However, in many contexts, foreign language education continues to ignore diversity in the classroom and fails to incorporate students’ linguistic resources (Bailey & Marsden, ; Hall & Cook, ; for the situation in German EFL classes, see Göbel & Helmke, ; Göbel & Vieluf, ), ultimately perpetuating monolingual practices. Failing to make use of these resources is not only detrimental to students with a migrant background but also to students of the majority population who cannot benefit from the linguistic resources of their peers.…”
Section: Introductionmentioning
confidence: 99%
“…Stattdessen werden sie als Problem beurteilt oder einfach ignoriert (Gogolin, 2019). Die Ressourcen von Lernenden mit vielfältigen Sprachlernerfahrungen werden in den Schulen bislang noch wenig produktiv genutzt Göbel & Vieluf, 2017). Die mangelnde Anerkennung der Plurilingualität der Lernenden und die bisweilen diskriminierende Behandlung der Familiensprachen wirkt sich negativ auf die soziale Eingebundenheit dieser Lernenden aus, kann Rückzugstendenzen von mehrsprachigen Lernenden in die eigene Kulturgemeinschaft verstärken und so auch die Anpassungsprozesse betroffener Schülerinnen und Schülern erschweren sowie weiterhin auch fachbezogene Lernprozesse negativ beeinflussen (Horenczyk, Jasinskaja-Lahti, Sam & Vedder, 2013).…”
Section: Mehrsprachigkeit Als Ressourceunclassified
“…Wenn Lehrpersonen die Sprachen ihrer Lernenden aufgreifen, dann geschieht dies zumeist unsystematisch (Heyder & Schädlich, 2015). Dabei werden mehrsprachigkeitsorientierte Vergleiche zumeist zur deutschen Sprache hergestellt (Göbel & Vieluf, 2017), weitere sprachliche Ressourcen der Lernenden werden am ehesten dann genutzt, wenn es sich um Prestigesprachen handelt (Mehlhorn, 2020). Dieser Sachverhalt wird einerseits auf das Fehlen mehrsprachigkeitsorientierter Aufgabenbeispiele in den Lehrwerken zurückgeführt, andererseits zeigen Untersuchungen, dass Lehrpersonen sich aufgrund von fehlenden sprachlichen Kompetenzen in den Herkunftssprachen der Lernenden unsicher fühlen (Schöpp, 2015).…”
Section: Mehrsprachigkeitsorientierung Im Unterrichtunclassified
“…Many studies on early FL learning conducted in European countries do not report any differences between minority language and majority language students in standardized comprehension or writing tests of the FL (e.g., Schoonen et al, 2003;Wilden & Porsch, 2016), and some studies even report significant disadvantages for minority language students as a group already at the primary school level (e.g., Elsner, 2007). However, when individual differences in cognitive skills and social background are controlled for, some selective advantages of minority language learners emerge (e.g., Hesse, Göbel, & Hartig, 2008;Maluch et al, 2015), yet multilingual boosts do not extend across all groups of learners (Göbel & Vieluf, 2017). In a recent study on German 9-10-year-old 3rd-and 4th-grade primary school minority and majority language students, Hopp, Vogelbacher et al (2019) reported that both cognitive and linguistic skills in the minority language contribute significantly to vocabulary and grammar skills in FL English.…”
Section: Plurilingual Foreign Language Teaching and Pedagogical Translanguagingmentioning
confidence: 99%